Number of ecological-trophic groups of microorganisms depending on technology of winter wheat cultivation on ordinary chernozem of the Central Caucasus - E. A. Menkina; N. N. Shapovalovа; A. A. Voropayeva (Юг России: экология, развитие, 2021)
Aim. To study the influence of cultivation technology on the number of ecological and trophic groups of microorganisms and the yield of winter wheat on the common chernozem of the Central Caucasus.Material and Methods. The number of microorganisms was determined by counting colonies on dense nutrient media according to generally accepted methods.Results. The number of microorganisms that transform organic and mineral forms of nitrogen and soil yeast was determined, depending on meteorological conditions, soil cultivation and fertilizers. Mineral fertilizers had the most significant effect on the activity of the soil microbiota. In years of varying moisture availability, fertilizers improved the nutrient regime of the soil, which contributed to increased plant development, microflora activity and increased winter wheat yield. In both the technologies applied, the largest number of all groups of microorganisms studied was observed when applying a complete mineral fertilizer -N52P52K52 .This dose of fertilizer also provided the highest yield of winter wheat - 6.07-6.33 t/ha. With a balanced plant nutrition regime (N52P52K52), the processes of decomposition and mineralization of plant residues proceeded at the same rate in both technologies. At the same time, without the use of fertilizers, the total activity of microorganisms in the no-till technology exceeded the minimum technology by 23.4х105 columnforming units, which indicates the beginning of the process of self-healing of the soil in the third year after the transition to direct sowing of crops.Conclusion. The number of microorganisms is one of the most sensitive indicators of the direction of complex biochemical processes, allowing us to assess the combined influence of all factors on the overall state of the soil microbiocenosis.